The contribution of climate smart interventions to enhance sustainable livelihoods in Chiredzi District - Defe, Rameck; Matsa, Mark (Elsevier, 2022)
Climate change impacts are exposing populations to many losses. Climate change impacts namely severe floods, droughts, extreme temperatures and storms are hindering attainment of sustainable livelihoods to most populations. This study sort to analyze the contribution of climate smart interventions targeting enhancement of sustainable livelihoods in Chiredzi District’s agricultural rural communities. Interventions have been implemented by Non-Governmental Organisations (NGOs) (CARE & PLAN) in collaboration with Government departments and communities. A pragmatist research philosophy encompassing both interpretivist (qualitative) and positivist (quantitative) paradigms was adopted to comprehensively answer research objectives. Household survey questionnaire was the main quantitative tool administered to randomly selected households. Interviews were conducted with purposively selected key informant interviewees from the Department of Agriculture Technical and Extension services, CARE, PLAN International, District Development Coordinator and Rural District Council. Adoption of climate smart interventions by 60.6% of the respondents in communities studied yielded notable successes whereby it enhanced sustainable livelihoods through ending poverty amongst vulnerable communities. Some, 67% of the respondents did fodder production to manage livestock production challenges induced by climate change. It also improved community well-being by increasing sources of livelihoods. The study recommends adoption of more climate smart interventions that ensures livelihood sustainability.